SOFC (Solid Oxide Fuel Cell) stack and method for converting methane into low-carbon hydrocarbon and generating electric energy
By forming a chemical modification layer on the surface of the martensite stainless steel connector of the SOFC battery stack and loading a methane oxidation coupling catalyst, combining oxygen ion-electron hybrid conductor materials, the problem of incompatibility between carbon deposits and anode materials in methane fuel is solved, and the problem of carbon deposits and anode materials is achieved. It can efficiently convert low-carbon hydrocarbons and generate electricity.
Patent Information
- Application Number
- CN202310699331.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
AI Technical Summary
When using methane as fuel in the existing SOFC battery stack, carbon deposits are easily formed on the surface of martensite stainless steel, resulting in gas path blockage, and traditional anode materials are incompatible with hydrocarbon fuels, making it difficult to efficiently convert low-carbon hydrocarbons and generate electricity.
Martensite stainless steel is used as the current collecting connector, and a chemical modification layer of gold or silver is formed on its surface. The anode side is supported by a methane oxidation coupling catalyst, combined with oxygen ion-electron hybrid conductor material to form a composite anode material to improve high-temperature chemistry Stability and catalytic activity.
It effectively inhibits carbon deposits, improves the yield and electricity generation of methane converted into low-carbon hydrocarbons, reduces manufacturing and operating costs, and enhances the safety and ethylene selectivity of the battery.
Smart Images

Figure CN119133495A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a SOFC cell stack and a method for converting methane into low-carbon hydrocarbons and generating electric energy, belonging to the technical field of SOFC and natural gas conversion and utilization. Background Art
[0002] The solid oxide fuel cell (SOFC) system is a device that can efficiently convert the chemical energy in the fuel into electrical energy, and has good prospects for commercial application. The fuel sources of the SOFC system are wide-ranging. In addition to hydrogen, hydrocarbon gases such as methane and propane can also be used as fuel. In recent years, with the large-scale development of methane-rich shale gas, natural gas hydrates, biogas, etc., replacing oil with relatively abundant and low-priced natural gas to produce basic chemicals such as ethylene has become a research and development focus in academia and industry. When the SOFC system uses methane as fuel, high-value-added products such as ethylene can be obtained by means of a composite methane oxidative coupling catalyst, achieving the goal of co-producing "low-carbon hydrocarbons-electricity".
[0003] The core of the SOFC system is the cell stack, which mainly includes tubular and flat types. Among them, the flat type SOFC stack has the advantages of high power density and low manufacturing cost, and has become the main development trend. The SOFC cell stack is composed of multiple basic cells connected in series. The connector is an important component, which plays the role of connecting the anode and cathode of adjacent single cells, providing current flow between adjacent cells, and preventing the mixing of gases on the cathode and anode sides to maintain the pressure balance in the stack. Therefore, the material used as the connector is generally required to have high conductivity and excellent mechanical and chemical stability, good air tightness, and similar thermal expansion coefficient to other components under high temperature conditions in oxidizing and reducing atmospheres. The operating temperature of traditional SOFC cell stacks is relatively high, and the connector is usually made of conductive ceramic materials, such as doped lanthanum chromate or stabilized zirconia. Due to the problems of difficult processing and high cost of ceramic materials, their application is limited. In recent years, with the reduction of operating temperature, metal materials have been widely used in SOFC stacks instead of ceramic materials. Metal connectors have the advantages of low cost, easy processing, and good conductivity.
[0004] There are many patent applications related to SOFC cell connectors, including improvements in connector material composition, design and manufacturing process. Some representative patents include: CN103872352A discloses a cell connector for a flat SOFC cell stack, which improves the power of the flat SOFC cell stack by optimizing the flow channel design of the connector and the inlet position of fuel and oxygen. CN203415644U discloses a new SOFC device, which mainly involves the structural design of a cell connector, wherein the disclosed connector is made of Fe-Cr-Y2O3 alloy, and a frame protruding to the front and back sides is provided around the connecting plate, and a wavy convex strip is provided on the front and back sides for guiding the gas to flow between the single cell unit and the connector. By optimizing the connector structure design, its uniform stability and oxidation resistance under airflow are improved. CN213071191U discloses a structural optimization method for a SOFC cell stack, which improves the force structure of the single cell by adding a metal clamp, so that the performance of the cell stack is stable and reliable. US5942349A describes a connector device for a flat-plate SOFC cell stack, which includes a flat chromium-containing substrate with a cathode-side airflow channel and a coating. The coating includes a spinel layer of at least one metal M (Mn, Fe, Co and Ni), which is located between the substrate and the oxide surface layer. The M oxide reacts with the surface chromium oxide on the substrate to form an intermediate spinel layer to enhance the stability of the SOFC. US9368810B2 discloses a connector device, which improves the air pressure imbalance problem between the air inlet and the air outlet by precisely controlling the air path depth of the connector, thereby enhancing the stability of the SOFC system. These prior arts are all aimed at improving the performance and durability of fuel cell stacks, reducing manufacturing costs, and making SOFC technology more commercially valuable.
[0005] US9452475B2 describes a method for chemically modifying the surface of a SOFC connector to prevent the chromium element in the connector alloy from contaminating the cathode material. The modified material used is mainly oxygen-conducting ceramic. When methane is used as the fuel for the SOFC system, the cell stack is prone to carbon deposits, especially in the metal connector part. However, most studies in the prior art are mainly focused on the corrosion and protection of connectors in a hydrogen atmosphere. The chemical modification mainly solves the problem of chromium element in stainless steel contaminating the cathode material, and less research is involved in the carbon deposition problem of the anode material.
[0006] In summary, the current existing technology usually uses micro or small button fuel cells for research, focusing on the characteristics of key battery materials such as cathode, anode, and electrolyte, and the currently reported SOFC systems usually use martensitic stainless steel as the material of the current collector and support system, and the main applicable fuels are hydrogen or synthesis gas. However, when this type of SOFC system directly uses hydrocarbon fuels, when the battery stack is operated at a higher temperature (>800℃), carbon deposits are easily formed on the surface of the martensitic stainless steel, which will cause gas path blockage.
[0007] Therefore, providing a new type of SOFC cell stack and a method for converting methane into low-carbon hydrocarbons and generating electrical energy has become a technical problem that urgently needs to be solved in the field. Summary of the invention
[0008] In order to solve the above-mentioned shortcomings and deficiencies, an object of the present invention is to provide a SOFC cell stack.
[0009] Another object of the present invention is to provide a method for converting methane into low-carbon hydrocarbons and generating electrical energy, which is achieved by using the above-mentioned SOFC cell stack. The present invention can efficiently convert methane into low-carbon hydrocarbons under non-reforming conditions, and convert the free energy of the reaction process into electrical energy.
[0010] In order to achieve the above objectives, on the one hand, the present invention provides a SOFC battery stack, comprising a plurality of battery stack basic units, each battery stack basic unit comprising an electrolyte, a cathode and an anode arranged on both sides of the electrolyte, a cathode current collecting layer and an anode current collecting layer respectively arranged on the cathode and the anode, and a current collecting connector connecting the cathode and the anode of adjacent battery stack basic units; wherein the material of the current collecting connector is martensitic stainless steel, and a chemical modification layer is arranged on both the cathode side and the anode side thereof, the material of the chemical modification layer on the anode side comprises gold or silver, preferably gold, and the material of the chemical modification layer on the cathode side comprises LSM, that is (La 0.80 Sr 0.20 ) 0.95 MnO 3-x LSCF, that is (La 0.60 Sr 0.40 ) 0.95 Co 0.20 Fe 0.80 O 3-x Or LSCM, that is, La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3-x , preferably LSM; wherein x represents the presence of oxygen vacancies, and the material has oxygen vacancies, so it can conduct oxygen ions at high temperatures;
[0011] The chemically modified layer on the anode side of the current collecting connector is loaded with a methane oxidative coupling catalyst.
[0012] As a specific embodiment of the SOFC cell stack described above in the present invention, the chemical modification layer can be formed by many methods including wet deposition, electrochemical deposition, sputtering deposition, etc., preferably electrochemical deposition or plasma sputtering deposition, and more preferably plasma sputtering deposition.
[0013] As a specific embodiment of the SOFC cell stack described above in the present invention, the thickness of the chemically modified layer is 1-50 μm, preferably 1-30 μm, and more preferably 5-10 μm.
[0014] As a specific embodiment of the SOFC cell stack described above in the present invention, the methane oxidative coupling catalyst is a cerium-manganese-tungsten catalyst, the active components of which include CeO2, Mn2O3 and Na2WO4, etc., and the carrier includes one or a combination of YSZ, ScSZ and GDC, etc.;
[0015] Based on the total weight of the active components being 100%, the active components include 0%-50% CeO2, preferably 10%-50% CeO2, 10%-40% Mn2O3 and 30%-70% Na2WO4.
[0016] As a specific embodiment of the SOFC cell stack described above in the present invention, a methane oxidative coupling catalyst is loaded on the chemically modified layer on the anode side of the current collecting connector, comprising:
[0017] The precursor of cerium, the precursor of manganese and the precursor of tungsten are dissolved in water, a carrier is added and continuously stirred and impregnated at room temperature, the liquid in the system is completely volatilized at 60-110° C., and then the dried solid is sintered at 750-900° C. for 4-12 hours in an air atmosphere, and then ground and sieved to less than 325 meshes to obtain a solid powder of methane oxidative coupling catalyst;
[0018] The solid powder of the methane oxidative coupling catalyst is uniformly mixed with the solvent to obtain a methane oxidative coupling catalyst slurry;
[0019] The methane oxidative coupling catalyst slurry is coated on the chemically modified layer on the anode side of the current collecting connector, and then dried to complete the loading of the methane oxidative coupling catalyst on the chemically modified layer on the anode side of the current collecting connector.
[0020] As a specific embodiment of the SOFC cell stack described above in the present invention, the mass fraction of the solid powder of the methane oxidative coupling catalyst is 30-70% based on the total weight of the methane oxidative coupling catalyst slurry being 100%. In some embodiments of the present invention, the solid powder of the methane oxidative coupling catalyst is uniformly mixed with the solvent in a mass ratio of 1:1 to obtain the methane oxidative coupling catalyst slurry, that is, based on the total weight of the methane oxidative coupling catalyst slurry being 100%, the mass fraction of the solid powder of the methane oxidative coupling catalyst is 50%.
[0021] The present invention does not make any specific requirements for the solvent used when loading the methane oxidative coupling catalyst on the chemically modified layer on the anode side of the current collector connector, and a conventional solvent used for making electrode slurry can be selected. For example, in some embodiments of the present invention, the solvent can be V-006A solvent purchased from Heraeus.
[0022] In some embodiments of the present invention, the current collecting connector is provided with a gas path groove away from the cathode or the anode, and the methane oxidative coupling catalyst is loaded on the chemically modified layer in the gas path groove to ensure that the current collecting connector can contact the anode, thereby ensuring the current collecting effect. At this time, the methane oxidative coupling catalyst slurry is coated on the chemically modified layer on the anode side of the current collecting connector, specifically including:
[0023] The methane oxidative coupling catalyst slurry is dripped onto the surface of the chemical modification layer on the anode side of the current collector connector, and the excess slurry on the surface is scraped off with a scraper to ensure that the slurry only exists in the gas path groove, and then placed in an oven for drying. After repeating three times, the methane oxidative coupling catalyst is loaded on the chemical modification layer on the anode side of the current collector connector, and the thickness of the methane oxidative coupling catalyst is the same as the depth of the gas path groove. Among them, the present invention does not make specific requirements on the drying temperature and time, which can be reasonably adjusted according to the actual needs of the on-site operation, such as the drying can be dried at 100°C for 1 hour.
[0024] As a specific embodiment of the SOFC battery stack described above in the present invention, the materials of the anode and the anode current collecting layer both include methane oxidative coupling catalytic active components and oxygen ion-electron mixed conductor materials, and the oxygen ion-electron mixed conductor material comprises a first component and a second component, the first component is a mixture of one or more of LSM, LSCF and LSCM, and the second component is a mixture of one or more of YSZ, i.e. yttrium stabilized zirconia, ScSZ, i.e. scandium stabilized zirconia and GDC, i.e. gadolinium-doped cerium oxide.
[0025] As a specific embodiment of the SOFC cell stack described above in the present invention, the mass fraction of the first component in the oxygen ion-electron mixed conductor material is 10%-90%, and the mass fraction of the second component is 10%-90%;
[0026] Preferably, the mass fraction of the first component in the oxygen ion-electron mixed conductor material is 50%-75%, and the mass fraction of the second component is 25%-50%.
[0027] As a specific embodiment of the SOFC cell stack described above in the present invention, the mass ratio of the methane oxidative coupling catalytic active component to the oxygen ion-electron mixed conductor material is 5:95-30:70;
[0028] Preferably, the mass ratio of the methane oxidative coupling catalytic active component to the oxygen ion-electron mixed conductor material is 12:88-27:73.
[0029] As a specific embodiment of the SOFC cell stack described above in the present invention, the methane oxidative coupling catalytic active component comprises a mixture of CeO2, Mn2O3 and Na2WO4;
[0030] The mass fraction of CeO2 in the methane oxidative coupling catalytic active component is 0%-50%, preferably 10%-50% CeO2, the mass fraction of Mn2O3 is 10%-40%, and the mass fraction of Na2WO4 is 30%-70%.
[0031] As a specific embodiment of the SOFC cell stack described above in the present invention, an anode is formed on one side of the electrolyte, comprising:
[0032] The precursor of cerium, the precursor of manganese and the precursor of tungsten are dissolved in water, a carrier is added and continuously stirred and impregnated at room temperature, the liquid in the system is completely volatilized at 60-110° C., and then the dried solid is sintered at 750-900° C. for 4-12 hours in an air atmosphere, and then ground and sieved to less than 325 meshes to obtain a solid powder of methane oxidative coupling catalyst;
[0033] The methane oxidative coupling catalyst solid powder, the first component and the solvent are uniformly mixed to obtain a composite anode material;
[0034] The composite anode material is coated on one side of the electrolyte and sintered at 1100-1200° C. for 1.5-6 hours to complete the production of the anode. In some embodiments of the present invention, the sintering may be, for example, sintering at 1100° C. for 6 hours, or sintering at 1200° C. for 90 minutes, or sintering at 1175° C. for 2 hours.
[0035] The anode materials of traditional SOFCs are mainly composite materials of metals (such as Ni, Pt, etc.) and oxygen-conducting ceramics (such as YSZ, GDC, etc.), and the applicable fuels are mainly hydrogen or synthesis gas. This anode material is not suitable for hydrocarbon fuels, because metal materials such as Ni in the anode will cause serious carbon deposition during the reaction, causing the battery performance to decline rapidly. For example, when the anode material is Ni / YSZ material, a higher sintering temperature (>1400°C) is usually required to ensure a good anode / electrolyte interface, and at this temperature the cathode material often loses its microporous structure, thus affecting performance. Therefore, the production of battery cells usually requires step-by-step sintering, that is, first sintering the anode at high temperature, coating the cathode after annealing, and sintering again at around 1200°C.
[0036] In this regard, in the SOFC battery stack provided by the present invention, the anode material includes a methane oxidative coupling catalytic active component and an oxygen ion-electron mixed conductor material, the oxygen ion-electron mixed conductor material includes a first component and a second component, the first component is a mixture of one or more of LSM, LSCF and LSCM, etc., the second component is a mixture of one or more of YSZ, ScSZ and GDC, etc., and the cathode material includes a mixture of one or more of LSM, LSCF or LSCM, etc. The composite anode material and the cathode material have similarities in components, and the cathode and the anode can be coated at the same time during the preparation of the battery sheet, and then sintered and formed at one time in a high temperature environment (for example, 1100°C-1200°C), thereby improving the battery yield and reducing the energy consumption of the battery manufacturing process; and the methane oxidative coupling catalytic active component is composited with the oxygen ion-electron mixed conductor material, while catalytically converting methane, inhibiting the occurrence of side reactions such as methane thermal cracking (producing carbon deposition) and water gas reforming, thereby improving the selectivity of hydrocarbon products. In addition, in the SOFC cell stack provided by the present invention, the metal material in the traditional SOFC anode material is replaced by a ceramic material, which can inhibit carbon deposition and avoid the problem of limited three-phase interface area of methane conversion in fuel cells using anode materials made of metal materials; on this basis, it is combined with a methane oxidative coupling catalytic active component to realize the direct conversion of methane to low-carbon hydrocarbons in SOFC and generate electricity at the same time. It has the advantages of low operating cost, good safety, high selectivity for ethylene, etc.
[0037] In addition, the anode current collecting layer of the existing SOFC is mostly made of metal powder slurry, and the metal powder may be, for example, Ni, Pt, Au or Ag. Among them, Ni and Pt are incompatible with hydrocarbons and will quickly catalyze the dehydrogenation reaction of hydrocarbons, causing serious carbon deposition; and the use cost of Au and Ag is relatively high, especially when applied to large-area battery stacks. In addition, the metal powder slurry only has electronic conductivity, but cannot conduct oxygen ions. In this regard, in the present invention, the material of the anode current collecting layer is methane oxidative coupling catalytic active components and oxygen ion-electron mixed conductor material. The use of mixed conductor material is low in cost on the one hand, and on the other hand, its excellent oxygen conductivity can expand the three-phase interface area of the battery anode catalytic reaction, which is beneficial to the catalytic reaction. Adding methane oxidative coupling catalytic active components to the anode current collecting layer can further expand the three-phase interface area of the catalytic reaction.
[0038] As a specific embodiment of the SOFC battery stack described above in the present invention, the anode current collecting layer is formed on the anode, comprising:
[0039] The precursor of cerium, the precursor of manganese and the precursor of tungsten are dissolved in water, a carrier is added and continuously stirred and impregnated at room temperature, the liquid in the system is completely volatilized at 60-110° C., and then the dried solid is sintered at 750-900° C. for 4-12 hours in an air atmosphere, and then ground and sieved to less than 325 meshes to obtain a solid powder of methane oxidative coupling catalyst;
[0040] The methane oxidative coupling catalyst solid powder, the first component and the solvent are uniformly mixed to obtain a composite anode material;
[0041] The composite anode material is coated on the anode and dried to form the anode current collecting layer. The present invention does not make specific requirements on the specific operation, temperature and time of drying, which can be reasonably adjusted according to the actual working conditions on site.
[0042] As a specific embodiment of the SOFC cell stack described above, the total thickness of the anode and the anode current collector is 60-120 μm, preferably 60-80 μm. In some embodiments of the present invention, the anode thickness ranges from 10-20 μm, and the anode current collector thickness ranges from 50-100 μm.
[0043] As a specific embodiment of the SOFC battery stack described above, the total thickness of the cathode and the cathode current collector is 60-120 μm, preferably 60-80 μm. In some embodiments of the present invention, the cathode thickness ranges from 10-20 μm, and the cathode current collector thickness ranges from 50-100 μm.
[0044] As a specific embodiment of the SOFC battery stack described above, the cathode and cathode current collecting layer are made of one of LSM, LSCF or LSCM, etc. In addition, the cathode current collecting layer can also be made of metals such as Pt, Au and Ag.
[0045] As a specific embodiment of the SOFC battery stack described above in the present invention, the material of the electrolyte includes a mixture of one or more of YSZ, ScSZ and GDC.
[0046] As a specific embodiment of the SOFC cell stack described above in the present invention, the SOFC cell stack further includes a sealing ring, the sealing ring is made of CaO-Al2O3-SiO2 glass ceramic, and the thickness of the sealing ring is 50-150 μm, preferably 60-80 μm.
[0047] The production process of the above-mentioned SOFC battery stack is common professional knowledge. For example, unless otherwise specified, the prepared cathode and anode materials are coated on both sides of the electrolyte sheet by screen printing, and the electrode thickness is 10-20μm after sintering at 1100-1200℃ for 1.5-6h. Gold glue and gold wire are used for current collection and electrical property measurement.
[0048] On the other hand, the present invention also provides a method for converting methane into light hydrocarbons and generating electrical energy, wherein the method utilizes the SOFC cell stack described above and comprises the following steps:
[0049] A first mixed gas containing oxygen is introduced into the cathode of the SOFC cell stack, and a second mixed gas containing methane is introduced into the anode thereof. The methane in the second mixed gas is converted into low-carbon hydrocarbons through the SOFC cell stack to generate electrical energy.
[0050] In some embodiments of the present invention, the method of converting methane into low-carbon hydrocarbons and generating electrical energy specifically includes: an oxygen-containing feed stream is purged through the cathode of the SOFC cell stack, an electrochemical reaction occurs, and oxygen ions are generated; the oxygen ions move through the electrolyte to the composite anode of the SOFC cell stack, and the composite anode contains an oxygen ion-electron mixed conductor material and a methane oxidative coupling catalytic active component. When the methane-containing feed stream is purged through the anode of the SOFC cell stack, methane undergoes a coupling reaction under the action of the oxygen ions and the methane oxidative coupling catalytic active components to generate low-carbon hydrocarbons and generate electrical energy at the same time.
[0051] As a specific embodiment of the above method of the present invention, the molar percentage of oxygen in the first mixed gas is not less than 15%;
[0052] The molar percentage of methane in the second mixed gas is 5%-80%, preferably 20%-80%.
[0053] As a specific implementation of the above method of the present invention, the balance gas in the first mixed gas is nitrogen; preferably, the first mixed gas is air.
[0054] As a specific implementation of the above method of the present invention, the balance gas in the second mixed gas is nitrogen and water vapor, and the molar percentage of the water vapor is 1%-10%.
[0055] As a specific embodiment of the above method of the present invention, the operating temperature of the SOFC cell stack is 700-1000°C, preferably 800-900°C.
[0056] Compared with the prior art, the beneficial technical effects that can be achieved by the present invention include:
[0057] 1) The present invention chemically modifies the surface of the current collector connector made of martensitic stainless steel in the SOFC cell stack to form a chemically modified layer, thereby improving its high-temperature chemical stability to hydrocarbon fuels such as methane and reducing the rate of carbon deposition, that is, effectively inhibiting the formation of carbon deposition on the surface, so that the SOFC cell stack can be directly operated in a methane atmosphere and generate electricity at the same time;
[0058] 2) The present invention increases the yield of methane conversion to low-carbon hydrocarbon products in the SOFC cell stack by loading / compounding a methane oxidative coupling catalyst on the chemically modified layer on the anode side of the current collecting connector.
[0059] 3) The basic unit of the SOFC cell stack provided by the present invention is an oxygen ion conductor fuel cell, which can highly selectively reduce the oxygen in the oxygen-containing feed stream (first mixed gas) into oxygen ions in situ during the reaction and provide them to the reaction system, thereby solving the need for an air pre-separation device in the traditional oxidative coupling reaction. In addition, the integration of the solid oxide fuel cell effectively avoids direct mixing between the methane-containing feed stream and the oxygen-containing feed stream, thereby improving the safety of the reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0061] Figure 1 It is a schematic cross-sectional view of a basic unit assembly in a SOFC cell stack provided in an embodiment of the present invention.
[0062] Figure 2In order to evaluate Example 1 of the present invention, the SOFC cell stack provided in Example 1 was disassembled to examine the carbon deposition on the anode side after the reaction.
[0063] Figure 3 In Example 1 of the present invention, the SOFC cell stack provided in Comparative Example 1 was disassembled to examine the carbon deposition on the anode side after the reaction.
[0064] Figure 1 Description of the main figures in the figure:
[0065] 1. Electrolytes;
[0066] 2. Anode;
[0067] 3. Cathode;
[0068] 4. Anode current collecting layer;
[0069] 5. Cathode current collecting layer;
[0070] 6. Au layer;
[0071] 7. LSM layer;
[0072] 8. Methane oxidative coupling catalyst;
[0073] 9. Sealing ring;
[0074] 10. Current collecting connector. DETAILED DESCRIPTION
[0075] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0076] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values listed are 1 and 2, and the maximum range values listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0077] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.
[0078] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.
[0079] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.
[0080] In the present invention, if not specifically stated, the term "two" used in this specification means "at least two".
[0081] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0082] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0083] Example 1
[0084] This embodiment provides a SOFC battery stack, including 5 single cells, and the cross-sectional schematic diagram of each single cell is as shown in FIG. Figure 1As shown, it includes an electrolyte 1, whose material is YSZ-8, a cathode 3 and an anode 2 arranged on both sides of the electrolyte, a cathode current collecting layer 5 and an anode current collecting layer 4 respectively arranged on the cathode 3 and the anode 2, and a current collecting connector 10 connecting the cathodes and anodes of adjacent single cells;
[0085] Wherein, an anode and a cathode are formed on both sides of the electrolyte, respectively, including:
[0086] Preparation of LSM / YSZ composite anode material slurry:
[0087] Weigh 8.208g Mn(NO3)3·4H2O, 5.058g Na2WO4·2H2O, 13.95g Ce(NO3)3·6H2O and dissolve them in 150mL deionized water. Add 19.2g YSZ powder under stirring. After continuous stirring and impregnation for 6h at room temperature, slowly concentrate at 80℃ until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 850℃ and sintered in air for 6h. Then grind and sieve to less than 325 mesh to obtain a solid powder of methane oxidative coupling catalyst. Weigh 5 g of the above-mentioned solid powder, 5 g of LSM powder (<325 mesh) and 10 g of V-006A solvent (the solvent required for making electrode slurry, purchased from Heraeus) and mix them evenly in an agate mortar to obtain LSM / YSZ composite anode material slurry. Based on the total weight of the LSM / YSZ composite anode material as 100%, its composition is 8.7% CeO2-4.1% Mn2O3-7.1% Na2WO4-30.1% YSZ-50% LSM.
[0088] Fabrication of cathode and anode:
[0089] By screen printing, LSM cathode material slurry (LSM20-I slurry purchased from FCM, in which the solid content of LSM is 62-72%) and the prepared LSM / YSZ composite anode material slurry are coated on both sides of the electrolyte sheet, and the cathode and anode are prepared after sintering at 1175°C for 2h to obtain a full battery, in which the thickness of the cathode is 20μm and the thickness of the anode is 15μm.
[0090] Then, a cathode current collecting layer and an anode current collecting layer are formed on the cathode and the anode of the full battery respectively, comprising:
[0091] The LSM cathode material slurry and the prepared LSM / YSZ composite anode material slurry were coated on both sides of the full battery, i.e., the cathode and anode sides of the full battery, respectively, by screen printing. After drying at 100°C for 1h, a cathode current collecting layer and an anode current collecting layer were formed, with thicknesses of 85μm and 80μm, respectively.
[0092] The material of the current collector connector is martensitic stainless steel, the cathode side of the current collector connector, that is, the side connected to the cathode, is plated with an LSM layer 7 by plasma sputtering deposition, with a thickness of 25 μm, and the anode side of the current collector connector, that is, the side connected to the anode, is plated with an Au layer 6 by plasma sputtering deposition, with a thickness of 10 μm; the chemical modification layer on the anode side of the current collector connector, that is, the Au layer, is loaded with a methane oxidative coupling catalyst 8, and the loading process specifically includes:
[0093] Preparation of methane oxidative coupling catalyst slurry:
[0094] Weigh 8.208g Mn(NO3)3·4H2O, 5.058g Na2WO4·2H2O, 13.95g Ce(NO3)3·6H2O and dissolve them in 150mL deionized water, and add 19.2g YSZ powder under stirring. After continuous stirring and impregnation at room temperature for 6h, slowly concentrate at 80℃ until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 850℃ and sintered in air for 6h. Then grind and sieve to less than 325 mesh to obtain a methane oxidative coupling catalyst solid powder, which has a composition of 5.9% CeO2-2.8% Mn2O3-4.9% Na2WO4-86.4% YSZ, based on the total weight of the methane oxidative coupling catalyst solid powder as 100%.
[0095] The above-mentioned methane oxidative coupling catalyst solid powder was evenly mixed with V-006A solvent (a solvent required for preparing electrode materials, purchased from Heraeus) in a mass ratio of 1:1 to obtain a methane oxidative coupling catalyst slurry.
[0096] The methane oxidative coupling catalyst slurry is coated on the Au layer on the anode side of the current collector connector. The coating step specifically includes: dripping the methane oxidative coupling catalyst slurry on the surface of the Au layer on the anode side of the current collector connector, and scraping off the excess slurry on the surface with a scraper (i.e., ensuring that the slurry only exists in the gas path groove), and then placing it in a 100° C. oven for drying for 1 hour. After repeating three times, the methane oxidative coupling catalyst is loaded on the chemically modified layer on the anode side of the current collector connector. The thickness of the methane oxidative coupling catalyst is the same as the depth of the gas path groove (1 mm). The loading amount of the methane oxidative coupling catalyst determined by differential weight method is 0.03 g / cm 2 .
[0097] In this embodiment, the sealing ring 9 used in the SOFC battery stack is made of CaO-Al2O3-SiO2 glass ceramics, and the thickness of the sealing ring is 95 μm; the total area of each single cell is 81 cm 2 , the effective current collecting area is 25cm 2 .
[0098] Example 2
[0099] This embodiment provides a SOFC cell stack, which differs from the SOFC cell stack provided in Embodiment 1 in the following aspects:
[0100] 1) The SOFC cell stack includes 2 single cells;
[0101] 2) The composite anode material is a LSCF / GDC composite anode material, and the preparation method of the slurry thereof includes:
[0102] Weigh 1.39g Mn(NO3)2·4H2O, 0.843g Na2WO4·2H2O, 2.33g Ce(NO3)3·6H2O and dissolve in 50mL deionized water, and add 3.2g GDC powder under stirring. After continuous stirring and impregnation for 6h at room temperature, slowly concentrate at 60℃ until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 900℃ and sintered in air for 4h. Then grind and sieve to less than 325 mesh to obtain a solid powder of methane oxidative coupling catalyst. Weigh 3g of the above powder, 7g LSCF powder (<325 mesh) and 10g V-006A solvent, mix them evenly in an agate mortar to obtain LSCF / GDC composite anode material slurry. Taking the total weight of the LSCF / GDC composite anode material as 100%, its composition is 5.2% CeO2-2.5% Mn2O3-4.2% Na2WO4-18.1% GDC-70% LSCF;
[0103] 3) The LSCF cathode material slurry and the prepared LSCF / GDC composite anode material slurry were respectively coated on both sides of the electrolyte sheet by screen printing, and the cathode and anode were prepared after sintering at 1150°C for 4.5h to obtain a full battery, wherein the thickness of the cathode was 20μm and the thickness of the anode was 10μm;
[0104] The material of the current collecting connector is martensitic stainless steel, the cathode side of the current collecting connector, that is, the side connected to the cathode, is plated with a LSCF layer by plasma sputtering deposition, with a thickness of 10 μm, and the anode side of the current collecting connector, that is, the side connected to the anode, is plated with an Au layer by plasma sputtering deposition, with a thickness of 10 μm;
[0105] 4) The cathode current collecting layer and the anode current collecting layer have thicknesses of 55 μm and 67 μm respectively;
[0106] 5) Preparation of methane oxidative coupling catalyst slurry:
[0107] Weigh 1.39g Mn(NO3)2·4H2O, 0.843g Na2WO4·2H2O, 2.33g Ce(NO3)3·6H2O and dissolve in 50mL deionized water, and add 3.2g GDC powder under stirring. After continuous stirring and impregnation at room temperature for 6h, slowly concentrate at 60°C until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 900°C and sintered in air for 4h. Then grind and sieve to less than 325 mesh to obtain a methane oxidative coupling catalyst solid powder. Taking the total weight of the methane oxidative coupling catalyst solid powder as 100%, its composition is: 17.3% CeO2-8.3% Mn2O3-14% Na2WO4-60.4% GDC;
[0108] 6) The thickness of the sealing ring is 75μm.
[0109] Example 3
[0110] This embodiment provides a SOFC cell stack, which differs from the SOFC cell stack provided in Embodiment 1 in the following aspects:
[0111] 1) The SOFC cell stack includes 2 single cells;
[0112] 2) The composite anode material is a LSCM / ScSZ composite anode material, and the preparation method of the slurry thereof includes:
[0113] Weigh 21.621g Mn(NO3)2·4H2O, 9.617g Na2WO4·2H2O, 4.329g Ce(NO3)3·6H2O and dissolve them in 150mL deionized water, and add 37g ScSZ powder under stirring. After continuous stirring and impregnation for 6h at room temperature, slowly concentrate at 110℃ until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 780℃ and sintered in air for 10h. Then grind and sieve to less than 325 mesh to obtain a solid powder of methane oxidative coupling catalyst. Weigh 7.5g of the above powder, 2.5g LSCM powder (<325 mesh) and 10g V-006A solvent (the solvent required for making electrode materials, purchased from Heraeus), mix them evenly in an agate mortar to obtain LSCM / ScSZ composite anode material slurry. Taking the total weight of the LSCM / ScSZ composite anode material as 100%, the composition thereof is 2.7% CeO2-10.8% Mn2O3-13.5% Na2WO4-58.4ScSZ-14.6% LSCM;
[0114] 3) The LSCM cathode material slurry and the prepared LSCM / ScSZ composite anode material slurry were respectively coated on both sides of the electrolyte sheet by screen printing, and the cathode and anode were prepared after sintering at 1100° C. for 6 h to obtain a full battery, wherein the thickness of the cathode was 20 μm and the thickness of the anode was 20 μm;
[0115] The material of the current collecting connector is martensitic stainless steel, the cathode side of the current collecting connector, that is, the side connected to the cathode, is plated with a LSCM layer by plasma sputtering deposition, with a thickness of 2 μm, and the anode side of the current collecting connector, that is, the side connected to the anode, is plated with an Ag layer by plasma sputtering deposition, with a thickness of 2 μm;
[0116] 4) cathode current collecting layer and anode current collecting layer, the thickness of which are 100 μm and 100 μm respectively;
[0117] 5) Preparation of methane oxidative coupling catalyst slurry:
[0118] Weigh 21.621g Mn(NO3)2·4H2O, 9.617g Na2WO4·2H2O, 4.329g Ce(NO3)3·6H2O and dissolve in 150mL deionized water, and add 37g ScSZ powder under stirring. After continuous stirring and impregnation at room temperature for 6h, slowly concentrate at 110°C until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 780°C and sintered in air for 10h. Then grind and sieve to less than 325 mesh to obtain a methane oxidative coupling catalyst solid powder, and the total weight of the methane oxidative coupling catalyst solid powder is 100%, and its composition is: 3.2% CeO2-12.6% Mn2O3-15.8% Na2WO4-68.4% ScSZ;
[0119] 6) The thickness of the sealing ring is 120 μm.
[0120] At the same time, a similar method was used to prepare (LSM+LSCF) / (YSZ+ScSZ) composite anode materials, (LSCF+LSCM) / (ScSZ+GDC) composite anode materials, (LSM+LSCM) / (YSZ+GDC) composite anode materials and (LSM+LSCF+LSCM) / (YSZ+ScSZ+GDC) composite anode materials, and single cells and SOFC cell stacks were constructed using the above composite anode materials.
[0121] Comparative Example 1
[0122] This comparative example provides a SOFC cell stack, which differs from the SOFC cell stack provided in Example 1 in the following aspects:
[0123] 1) The SOFC cell stack includes 2 single cells;
[0124] 2) The current collecting connector has not been surface treated, that is, no chemical modification layer is provided on the current collecting connector, and no methane oxidative coupling catalyst is loaded.
[0125] Comparative Example 2
[0126] This comparative example provides a SOFC cell stack, which differs from the SOFC cell stack provided in Example 1 in the following aspects:
[0127] 1) The SOFC cell stack includes 2 single cells;
[0128] 2) The current collecting connector has not been surface treated, that is, no chemical modification layer is provided on the current collecting connector, and no methane oxidative coupling catalyst is loaded;
[0129] 3) The composite anode material is a YSZ composite anode material, and the preparation method of the slurry thereof includes:
[0130] Weigh 0.71g Mn(NO3)2·4H2O, 0.42g Na2WO4·2H2O, 1.15g Ce(NO3)3·6H2O and dissolve in 50mL deionized water, and add 4.0g YSZ powder under stirring. After continuous stirring and impregnation for 6h at room temperature, slowly concentrate at 80℃ until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 850℃ and sintered in air for 6h. Then grind and sieve to less than 325 mesh to obtain a solid powder of methane oxidative coupling catalyst. Weigh 4g of the above powder and 4g of V-006A solvent in an agate mortar and mix them evenly to obtain a YSZ composite anode material slurry. Taking the total weight of the YSZ composite anode material as 100%, its composition is 9.0% CeO2-4.4% Mn2O3-7.4% Na2WO4-79.2% YSZ.
[0131] Comparative Example 3
[0132] This comparative example provides a SOFC cell stack, which differs from the SOFC cell stack provided in Example 1 in the following aspects:
[0133] 1) The SOFC cell stack includes 2 single cells;
[0134] 2) The current collecting connector has not been surface treated, that is, no chemical modification layer is provided on the current collecting connector, and no methane oxidative coupling catalyst is loaded;
[0135] 3) The composite anode material is a LSCF / GDC composite anode material, but during preparation, the ceramic solid material is first mixed and then impregnated. The specific preparation method of the slurry includes:
[0136] Weigh 4.104g Mn(NO3)2·4H2O, 2.529g Na2WO4·2H2O, 6.97g Ce(NO3)3·6H2O and dissolve them in 100mL deionized water. Weigh 10g GDC powder and 34g LSCF powder, stir them evenly in agate grinding, and then pour them into the catalyst aqueous solution under stirring. After continuous stirring and impregnation for 6h at room temperature, slowly concentrate at 80℃ until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 850℃ and sintered in air for 6h. Then grind and sieve to less than 325 mesh to obtain solid powder. Weigh 10g of the above powder and mix it evenly with 10g V-006A solvent in an agate mortar to obtain LSCF / GDC composite anode material slurry. Based on the total weight of the LSCF / GDC composite anode material being 100%, the composition thereof is 5.5% CeO2-2.6% Mn2O3-4.5% Na2WO4-19.9% GDC-67.5% LSCF.
[0137] Comparative Example 4
[0138] This comparative example uses Ni|YSZ|LSM full cells purchased directly from Soforen to assemble a dual-cell stack, that is, a fuel cell stack is constructed using a traditional nickel-containing anode, and its methane oxidative coupling reaction performance is examined.
[0139] The fuel cell stack is a dual-cell stack, with a total area of 81cm per single cell. 2 , the effective current collecting area is 25cm 2 .
[0140] Evaluation Example 1
[0141] This evaluation example performs performance evaluation on the SOFC cell stacks provided in Example 1 and Comparative Example 1, respectively, including:
[0142] First, the SOFC cell stacks provided in Example 1 and Comparative Example 1 were transferred to a fuel cell stack test stand. A pressure of 25 kg / cell was applied. After standing at room temperature for 4-6 hours, the gas circuit was connected, and 100-1000 mL / min of nitrogen was introduced into the cathode and anode at the same time.
[0143] Under nitrogen protection, the battery stack was heated to 800°C at a rate of 1°C / min. At this time, the system pressure would drop slightly due to the softening and collapse of the sealing ring due to heat. The pressure was readjusted to 25kg / cell and static pressure was maintained for 2-4 hours. During this period, the leakage was observed. After the system was airtight, it was gradually switched to the reaction atmosphere and measurement began.
[0144] For the SOFC cell stack provided in Example 1, its operating temperature is 850° C., the gas pressure inside the cell stack is 1 atm, the anode feed is methane 250 mL / min, nitrogen 150 mL / min, containing 3% water vapor, and the cathode feed is air 8 L / min.
[0145] For the SOFC cell stack provided in Comparative Example 1, the stack operating temperature is 850°C, the internal gas pressure of the stack is 1 atm, the anode feed is methane 100 mL / min, nitrogen 50 mL / min, containing 3% water vapor, and the cathode feed is air 2 L / min.
[0146] The catalytic reaction products were detected by online gas chromatography to calculate the conversion rate, product selectivity, etc. The fuel cell performance was evaluated by linear voltammetry and electrochemical impedance spectroscopy.
[0147] Methane conversion rate (%) = (C 2+ Carbon content of hydrocarbons + carbon content of CO + carbon content of CO2) / total carbon content of gas phase products*100%;
[0148] Hydrocarbon selectivity (%) = hydrocarbon carbon content / total carbon content of gas phase products*100%.
[0149] After testing, the power generation power of the SOFC cell stack provided in Example 1 is 4.9W, and the power density is 392W / m 2 The methane conversion rate is 38.62%, the ethylene selectivity is 34.25%, the ethane selectivity is 9.56%, and the rest is CO or CO2. The initial power of the SOFC cell stack provided in Comparative Example 1 is 10W, and the power density is 2000W / m 2 The conversion rate of methane is 99.3%, and the gaseous products are 8.8% CO2 and 91.2% CO, with no hydrocarbon products.
[0150] After the test, the SOFC cell stacks provided in Example 1 and Comparative Example 1 were disassembled respectively. For the SOFC cell stack provided in Example 1, the carbon deposition on the anode side after the reaction was as follows: Figure 2 As shown, from Figure 2 The gold coating can be clearly seen, and the large black area is not carbon deposits, but the anode material peeled off onto the current collector during the disassembly process. For the SOFC cell stack provided in Comparative Example 1, the carbon deposits on the anode side after the reaction are as follows Figure 3 As shown, from Figure 3 It can be observed that there is obvious carbon deposition on the anode side after the reaction and the power decays rapidly.
[0151] Evaluation Example 2
[0152] This evaluation example refers to the method in evaluation example 1 to evaluate the performance of the SOFC cell stacks provided in examples 2-3 and comparative examples 2-4:
[0153] For the SOFC cell stack provided in Example 2, the test temperature is 830°C and the pressure is 1 atm. The anode feed is methane 100 mL / min, nitrogen 200 mL / min, containing 3% water vapor, and the cathode feed is air 4 L / min. When the power generation is 2.10 W, the cell power density is 420 W / m 2 , the methane conversion rate is 21.22%, the ethylene selectivity is 28.47%, the ethane selectivity is 10.78%, and the rest is CO or CO2.
[0154] For all SOFC cell stacks provided in Example 3, the test temperature is 900°C and the pressure is 1 atm. The anode feed is methane 160 mL / min, nitrogen 40 mL / min, containing 9% water vapor, and the cathode feed is oxygen 0.75 L / min, nitrogen 4.25 L / min. When the power generation is 1.86 W, the cell power density is 372 W / m 2 The methane conversion rate is 35.85%, the ethylene selectivity is 25.01%, the ethane selectivity is 7.37%, and the rest is CO or CO2.
[0155] For the SOFC cell stack provided in Comparative Example 2, the test temperature is 900°C, the anode feed is methane 50mL / min, nitrogen 200mL / min, containing 3% water vapor, and the cathode feed is air at a flow rate of 2L / min. At an output power of -1.2W (i.e., an additional electrical energy of 240W / m 2 ), the methane conversion rate is 26.2%, the ethylene selectivity is 17.6%, the ethane selectivity is 2.1%, and the remaining products are CO or CO2.
[0156] Since the YSZ composite anode material in Comparative Example 2 does not contain conductive substances, the internal resistance of the SOFC stack constructed therefrom is relatively large, and the electromotive force of the chemical reaction of the reactants on both sides of the battery alone cannot provide a sufficiently large current (or oxygen flux). In order to achieve sufficient oxygen flux, additional electrical energy must be added, and the SOFC stack requires a relatively high operating temperature.
[0157] For the SOFC cell stack provided in Comparative Example 3, the test temperature is 850°C, the anode feed is 20% CH4-80% N2, the flow rate is 50 mL / min, and the cathode feed is air, the flow rate is 500 mL / min. When the output power is -0.7 W (i.e., additional electrical energy), the methane conversion rate is 15.2%, the ethylene selectivity is 21.3%, the ethane selectivity is 5.6%, and the remaining products are CO or CO2.
[0158] The LSCF / GDC composite material prepared by the method in Comparative Example 3 is prepared by first mixing LSCF powder with GDC powder and then compounding with the catalyst. Such a synthesis sequence results in a large amount of insulating catalyst material being deposited on the surface of LSCF, which affects the conductivity of LSCF and even the entire anode material, thereby increasing the overall internal resistance of the battery, and requiring additional electrical energy to achieve sufficient oxygen flux.
[0159] For the SOFC cell stack provided in Comparative Example 4, the test temperature was 800°C and the pressure was 1 atm. The anode feed was methane 100 mL / min, nitrogen 200 mL / min, and the cathode feed was air 2 L / min. The system had severe carbon deposition, the gas phase methane conversion rate was 3.7%, the CO selectivity was 90.3%, the CO2 selectivity was 9.7%, and no low-carbon hydrocarbons were generated.
[0160] In the battery stack constructed with the traditional metal-containing anode material in Comparative Example 4, methane is easily catalytically decomposed on the surface of nickel to form carbon black and hydrogen. Carbon black deposition causes the pores of the battery anode to be blocked, and further blocks the gas path of the battery stack. At the same time, carbon black is not a good catalyst for the methane conversion reaction at a reaction temperature of 800°C, resulting in a significant decrease in the methane conversion rate.
[0161] In summary, in the embodiments of the present invention, a chemical modification layer is formed on the surface of the current collecting connector made of martensitic stainless steel and a methane oxidative coupling catalyst is loaded on the chemical modification layer on the anode side of the current collecting connector, thereby effectively inhibiting the formation of surface carbon and increasing the yield of methane conversion to generate low-carbon hydrocarbon products.
[0162] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.
Claims
1. A SOFC battery stack, comprising a plurality of battery stack basic units, each battery stack basic unit comprising an electrolyte, a cathode and an anode arranged on both sides of the electrolyte, a cathode current collecting layer and an anode current collecting layer respectively arranged on the cathode and the anode, and a current collecting connector connecting the cathodes and anodes of adjacent battery stack basic units; characterized in that: The material of the current collecting connector is martensitic stainless steel, and the cathode side and the anode side thereof are both provided with chemical modification layers, the material of the chemical modification layer on the anode side includes gold or silver, and the material of the chemical modification layer on the cathode side includes LSM, LSCF or LSCM; The chemically modified layer on the anode side of the current collecting connector is loaded with a methane oxidative coupling catalyst.
2. The SOFC cell stack according to claim 1, characterized in that: The thickness of the chemically modified layer is 1-50 μm, preferably 1-30 μm.
3. The SOFC cell stack according to claim 1, characterized in that: The methane oxidative coupling catalyst is a cerium-manganese-tungsten catalyst, whose active components include CeO2, Mn2O3 and Na2WO4, and the carrier includes one or a combination of YSZ, ScSZ and GDC; Based on the total weight of the active components being 100%, the active components include 0%-50% CeO2, 10%-40% Mn2O3 and 30%-70% Na2WO4.
4. The SOFC cell stack according to claim 1 or 3, characterized in that: A methane oxidative coupling catalyst is loaded on the chemically modified layer on the anode side of the current collecting connector, comprising: The precursor of cerium, the precursor of manganese and the precursor of tungsten are dissolved in water, a carrier is added and continuously stirred and impregnated at room temperature, the liquid in the system is completely volatilized at 60-110° C., and then the dried solid is sintered at 750-900° C. for 4-12 hours in an air atmosphere, and then ground and sieved to less than 325 meshes to obtain a solid powder of methane oxidative coupling catalyst; The solid powder of the methane oxidative coupling catalyst is mixed evenly with the solvent to obtain a methane oxidative coupling catalyst slurry; The methane oxidative coupling catalyst slurry is coated on the chemically modified layer on the anode side of the current collecting connector, and then dried to complete the loading of the methane oxidative coupling catalyst on the chemically modified layer on the anode side of the current collecting connector.
5. The SOFC cell stack according to claim 1, characterized in that: The materials of the anode and the anode current collecting layer both include methane oxidative coupling catalytic active components and oxygen ion-electron mixed conductor materials, and the oxygen ion-electron mixed conductor materials include a first component and a second component, the first component is a mixture of one or more of LSM, LSCF and LSCM, and the second component is a mixture of one or more of YSZ, ScSZ and GDC.
6. The SOFC cell stack according to claim 5, characterized in that: The mass fraction of the first component in the oxygen ion-electron mixed conductor material is 10%-90%.
7. The SOFC cell stack according to claim 5, characterized in that: The mass ratio of the methane oxidative coupling catalytic active component to the oxygen ion-electron mixed conductor material is 5:95-30:
70.
8. The SOFC cell stack according to claim 5, characterized in that: The methane oxidative coupling catalytic active component comprises a mixture of CeO2, Mn2O3 and Na2WO4; The mass fraction of CeO2 in the methane oxidative coupling catalytic active component is 0%-50%, the mass fraction of Mn2O3 is 10%-40%, and the mass fraction of Na2WO4 is 30%-70%.
9. The SOFC cell stack according to any one of claims 5 to 8, characterized in that: An anode is formed on one side of the electrolyte, comprising: The precursor of cerium, the precursor of manganese and the precursor of tungsten are dissolved in water, a carrier is added and continuously stirred and impregnated at room temperature, the liquid in the system is completely volatilized at 60-110° C., and then the dried solid is sintered at 750-900° C. for 4-12 hours in an air atmosphere, and then ground and sieved to less than 325 meshes to obtain a solid powder of methane oxidative coupling catalyst; The methane oxidative coupling catalyst solid powder, the first component and the solvent are uniformly mixed to obtain a composite anode material; The composite anode material is coated on one side of the electrolyte and sintered at 1100-1200° C. for 1.5-6 hours to complete the production of the anode.
10. The SOFC cell stack according to claim 1 or 5, characterized in that: Forming the anode current collecting layer on the anode comprises: The precursor of cerium, the precursor of manganese and the precursor of tungsten are dissolved in water, a carrier is added and continuously stirred and impregnated at room temperature, the liquid in the system is completely volatilized at 60-110° C., and then the dried solid is sintered at 750-900° C. for 4-12 hours in an air atmosphere, and then ground and sieved to less than 325 meshes to obtain a solid powder of methane oxidative coupling catalyst; The methane oxidative coupling catalyst solid powder, the first component and the solvent are uniformly mixed to obtain a composite anode material; The composite anode material is coated on the anode and dried to form the anode current collecting layer.
11. The SOFC cell stack according to claim 1 or 5, characterized in that: The total thickness of the anode and the anode current collecting layer is 60-120 μm.
12. The SOFC cell stack according to claim 1, characterized in that: The total thickness of the cathode and the cathode current collecting layer is 60-120 μm.
13. The SOFC cell stack according to claim 1, characterized in that: The material of the cathode and the cathode current collecting layer includes one of LSM, LSCF or LSCM.
14. The SOFC cell stack according to claim 1, characterized in that: The material of the electrolyte includes a mixture of one or more of YSZ, ScSZ and GDC.
15. The SOFC cell stack according to claim 1, characterized in that: The SOFC cell stack further comprises a sealing ring, the material of the sealing ring is CaO-Al2O3-SiO2 glass ceramic, and the thickness of the sealing ring is 50-150 μm.
16. A method for converting methane into light hydrocarbons and generating electrical energy, characterized in that: The method utilizes the SOFC cell stack according to any one of claims 1 to 15, and comprises the following steps: A first mixed gas containing oxygen is introduced into the cathode of the SOFC cell stack, and a second mixed gas containing methane is introduced into the anode thereof, and the methane in the second mixed gas is converted into low-carbon hydrocarbons through the SOFC cell stack to generate electrical energy.
17. The method according to claim 16, characterized in that The molar percentage of oxygen in the first mixed gas is not less than 15%; The molar percentage of methane in the second mixed gas is 5%-80%.
18. The method according to claim 16 or 17, characterized in that The operating temperature of the SOFC cell stack is 700-1000°C.
Citation Information
Cited By
Current collecting layer on air electrode side of solid oxide cell stack, and preparation method and application of current collecting layer
CN120356968A
A current collector for the air electrode side of a solid oxide cell stack, a method for producing the same and use thereof
CN120356968B
